Arabic or English? Multilingual users’ preferences in Dubai ATM transactions - Al-Issa, Ahmad; Sulieman, Hana (Frontiers in Communication, 2024)
Language choice or preference, that is, the deliberate selection of language(s) for different purposes in different contexts, situations and domains, is a complex sociolinguistic phenomenon as it is usually motivated by numerous sociolinguistic factors. This study investigates language choice between Arabic and English during automated teller machine (ATM) transactions in Dubai, a cosmopolitan city in the United Arab Emirates (UAE), and aims at exploring the factors influencing these preferences. The data were collected, using a survey questionnaire, from 566 ATM users in Dubai. The findings reveal that nearly all non-Arab participants favor English over Arabic for ATM transactions, irrespective of their length of stay in the country and their proficiency level in English and Arabic, given that Dubai ATMs offer only these two languages. On the other hand, Arab participants, including UAE nationals and Arab expatriates, tend to use Arabic more frequently than English. However, those residing in Dubai show a greater preference for English compared to those living outside Dubai. Additional factors such as age, gender, level of education, occupation, and comfort with technology were also investigated. This research illuminates the prevalent use and elevated status of English in Dubai, affirming its significance among both native and non-native Arabic speakers. Furthermore, it offers insight into the linguistic resources employed by individuals in transactional exchanges, contributing to our understanding of the complex relationship between language contact, language attitudes, language choice, and technology adoption within a multilingual urban setting. The findings underscore the importance of examining linguistic preferences within specific subdomains of multilingual communities.